Is Early Sex Reassignment in Ambiguous Genitalia Reasonable? - E Shirazi; Z Shahrivar; B Ghorbani (JRI, 2010)
Introduction: Ambiguous genitalia is a medical emergency in newborns and effort is made to perform sex reassignment and reconstructive surgery as soon as possible. However, conflict between the assigned sex and later gender identity are still present in many cases. This discrepancy between sexual and gender identities leads to several complications that are the focus of the present study. Materials and Methods: The literature review was performed by searching some knowledge-based databases such as Medline/PubMed (from the National Library of Medicine), Scopus, PsyClic and the Iranian Scientific Information Database (SID) on the internet and all the available articles in relevant journals published up to August 2009. Results: A significant number of intersex individuals suffer from incoherence between the sex reassigned to them by the medical team, and their gender identity revealed to them in teen ages or adulthood. As an adult, a large number of these individuals do not live according to their early reassigned sex and some may seek further sex reassignment congruent to their gender identity. A number of these cases have spoken out against the treatments performed during their childhood. They believe that the current treatment strategies for intersex individuals are paternalistic and incompatible with codes of medical ethics and human rights. Conclusion: The current knowledge about the complexities of sexual identity development, gender identity, gender role and sexual orientation is sparse and incomprehensive. The current approach for the management of infants with ambiguous genitalia seems to need major reevaluation. It seems better to defer any sex reassignment and reconstructive surgery until their gender is revealed and they are legally eligible to decide about these issues by themselves.
Keywords: Ambiguous Genitalia, Gender Identity, Intersex, Reconstructive Surgery, Sex reassignment